Influence Of Marketing Mix (Marketing Mix) On Consumer Purchase Decisions Cachet Products In Kendari City (Case Study Of UD. Cashew Mubaraq Lombe Kendari City) - Noval Ivandri Renggaala; Sarinah Sarinah; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine the effect of the marketing mix on purchasing decisions at UD. Cashew Mubaraq Lombe, Lahundape Village, West Kendari District, Kendari City. Determination of the research location is done purposively. Data was collected by using questionnaires, interviews, and documentation methods. The analysis used multiple regression analysis. Results Based on research analyzing the marketing mix of UD cashew products. Cashew Mubaraq Lombe Kendari City. The results showed that the assessment of the aspects of the marketing mix (product, price, and place) had an outstanding rating category where the average consumer chose an answer score of 4 or agreed. In contrast, the marketing mix (promotion) aspect had a poor rating category where the average consumer chooses an answer score of 3 or less to agree and two or disagree. The results of processing and computerization using SPSS version 15 show the effect of purchasing decisions on aspects of the marketing mix (product, price, place, promotion) by obtaining the Fount Ftable and significant value <0.1. The results of the F test (simultaneous) show that the study has a simultaneous effect on the product, price, place, and promotion variables on product purchasing decisions. While the t-test results (partial) on the product, price, place, and promotion variables affect purchasing decisions cashew products UD. Cashew Mubaraq Lombe Kendari City, the variable that has a more dominant influence on purchasing decisions is the price variable which shows the t-count value is greater than the table (8.231517 > 1.65657), or sig, < a (0.00000001 < 0.1.